Effect of land and aquatic medicine ball training on shoulder imbalance among water polo players - Nekooei, Pooya (2020)
This study aimed to investigate the effect of land and aquatic medicine ball training on bilateral shoulder strength imbalance and their impact on throwing velocity and accuracy in male water polo players. The relationship of shoulder strength imbalance and anthropometric variables with throwing velocity and accuracy among water polo players was also examined. Participants in this study were Malaysian male elite water polo players (N=42), aged 16.79 ± 1.77 years old. They were randomly assigned equally to three groups (Aquatic and land training (n=14 for each) and a control group (n= 14) using the Fishbowl technique. A pretest and three posttests research design were used in the present study. The experimental groups for land and aquatic undergo same specific training on the non-dominant hand with gradually increasing load in every three weeks for 9 weeks (starting with normal water polo ball, 1kg and 2 kg medicine ball). This is an addition to their usual water polo training, while the control group only attended usual water polo training similar to the experimental groups. The training protocol used was the same for both land and aquatic training to evaluate the effect of training and different loads on shoulder imbalance rectification. After the completion of each three weeks of the intervention, eight tests of shoulder movement strength and two tests of throwing performance were administered to all participants to measure their changes in shoulder strength imbalance, throwing velocity and throwing accuracy. The paired sample t test of the pre test scores indicated that there were significant differences between the players' dominant hand and their non dominant hand in all eight shoulder movements strength for all players, where Flexion (t= 136.09 and p< .001), Extension (t= 110.92 and p< .001), Abduction (t= 121.89 and p< .001), Adduction (t= 101.47 and p< .001), Horizontal Adduction (t= 92.3 and p< .001), Horizontal Abduction (t= 95.6 and p< .001), Internal Rotation (t= 109.6 and p< .001) and External Rotation (t= 102.18 and p< .001). The results of repeated measures MANOVA showed a statistically significant difference in the mean test scores of shoulder strength imbalance in the pretest and 3 follow-up test measurements of both land and aquatic groups after 9 weeks non dominant hand training. Both experimental groups showed statistically significant improvement within and between groups on shoulder imbalance rectification. The results of between group comparison showed 93% for aquatic group and 43% for the land group’s mean difference improvement from pretest to posttest. Throwing velocity and accuracy of the players showed significant improvement as well after 9 weeks of training. However, the improvement between land and aquatic groups in throwing velocity and accuracy were not significant. The findings of the study showed that water polo players have a tendency of bilateral shoulder imbalance which influence their throwing performance. The results also show that an intervention of specific training of 9 weeks of non-dominant hand by using medicine ball training on land and in water was effective in changing shoulder strength imbalance in the players. Hence, increasing water polo players’ non-dominant hands’ strength helps in rectifying the shoulder imbalance and these will be beneficial in improving their throwing performance.